Tradisi Masyarakat Agraris di Desa Bojongsari dan Sukamaju Kecamatan Nyalindung Sukabumi - Supendi, Usman; Sopiah, Eva (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In the existence of a cultured society, of course there are various kinds of customs or traditions that arise due to existing knowledge. Likewise with agricultural societies. Indonesia itself is the largest agricultural country ever in recorded Asian history. Especially in the rice agricultural sector. For hundreds of years, Indonesia has been the largest rice contributing country. Especially in Parahyangan or what we usually call West Java. This Sundanese people have implemented customs in the agricultural sector starting hundreds of years ago. Seren Taun is a traditional ceremony to commemorate harvest day. We can still find this ceremony and preserve it in traditional villages such as Kanekes Baduy Village, Ciptagelar Village in Sukabumi, Cigugur Village in Kuningan and other traditional villages. In this case, it turns out that we can not only find Seren Taun customs in villages or traditional villages, but we can still find them in inland villages. Examples are Bojongsari Village and Sukamaju Village in Nyalindung sub-district, Sukabumi district. The Seren Taun traditional ceremony held in Bojongsari and Sukamaju villages itself has significant differences from the Seren Taun custom in traditional villages. This traditional ceremony has gone through various kinds of acculturation, both in terms of social culture and religion.